A phone of our own : the deaf insurrection against Ma Bell - Lang, Harry G. (Gallaudet University Press, 2000)
In 1964, of the more than 85 million telephones in the United States and Canada, less than one percent were used regularly by deaf people. If they didn't ask their hearing neighbors for help, they depended upon their hearing children, some as young as three years old, to act as intermediaries for business calls or medical consultations. In that same year, three enterprising deaf men, Robert H. Weitbrecht, James C. Marsters, and Andrew Saks, started the process that led to deaf people around the world having an affordable phone system that they could use. Weitbrecht, a successful physicist with the Stanford Research Institute, had been experimenting with a teletypewriter (TTY) used with shortwave radios. When Marsters, a prominent deaf orthodontist, met Weitbrecht and saw his TTY, he immediately suggested the possibility of resolving deaf people's decades-long struggle to have access to telecommunications without relying totally upon hearing people as go-betweens. Andrew Saks brought his business acumen to the group, which soon set to work overcoming the daunting problems they faced. Harry G. Lang's A Phone of Our Own: The Deaf Insurrection Against Ma Bell tells how these three men collaborated to solve the technical difficulties of developing a coupling device for TTYs that would translate sounds into discernible letters. More remarkably, and with the help of an expanding corps of Deaf advocates, they successfully assaulted the American Telephone and Telegraph Company (AT&T), which in its efforts to protect its monopoly, smashed old TTYs to keep them from being used for potentially competitive purposes. The Federal Communications Commission (FCC) also resisted efforts to build a telephone system for deaf people that was available, affordable, portable, and fully accessible. Lang recounts in vivid terms how many other Deaf individuals and groups from all walks of life joined Weitbrecht, Marsters, and Saks against these forces. A Phone of Our Own is an entertaining and engrossing story of how they fought and won, and changed the world for the better for deaf people everywhere.